2021
DOI: 10.1002/ejoc.202100526
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Natural Rubrolides B, I, K, L, M, O and Analogues

Abstract: The chlorinated natural products, rubrolides B, I, K, L, M and O and analogues were synthesized in only five steps employing a robust and divergent synthetic strategy. The synthesis is performed without using protecting groups starting from a key intermediate, which can be synthesized from commercially available tetronic acid in only two steps. Selective halogenation and vinylogous aldol condensation enable the efficient synthesis of highly halogenated natural occurring rubrolides as well as synthetic analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The same study also demonstrated for the first time that diorcinols can cause a 54% reduction of S. maltophilia K279a (here referred to as K279a) biofilms; therefore, diorcinols seem to be promising antibiofilm substances. Additionally, we also previously demonstrated that rubrolides had a significant antibiofilm activity against K279a ( 37 ).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The same study also demonstrated for the first time that diorcinols can cause a 54% reduction of S. maltophilia K279a (here referred to as K279a) biofilms; therefore, diorcinols seem to be promising antibiofilm substances. Additionally, we also previously demonstrated that rubrolides had a significant antibiofilm activity against K279a ( 37 ).…”
Section: Introductionmentioning
confidence: 66%
“… S. maltophilia is highly resistant against most antibiotics, and, as consequence, biofilms of clinical isolates are very difficult to treat. Recently, we showed that diorcinols and rubrolides strongly reduced biofilm formation of S. maltophilia K279a ( 36 , 37 ). Intrigued by this initial and encouraging observation, we asked if we could identify individual genes and pathways involved in biofilm inhibition and what the impact was on the overall biofilm architecture and gene expression profiles of S. maltophilia biofilms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology is faster and with lower cost than other methodologies described in the literature to provide direct access to -(hydroxyaryl)butenolides which have biological properties 7,22 and are synthons for the synthesis of more complex compounds. 4,23,24…”
Section: Letter Synlettmentioning
confidence: 99%
“…The -arylbutenolide moiety is present in several natural and synthetic products that have important biological properties such as congestive heart failure, 1 antiviral and antimicrobial properties, [2][3][4] inhibitor of tumor necrosis factor (TNF-), 5 inhibitor of BACE, 6 and antitumor activity 7 (Figure 1).…”
mentioning
confidence: 99%